The Transmission Network of Qirā’āt Knowledge: The Genealogy of the Sanad of Arab-Indonesian Scholars and the Dominance of the Riwayat Hafs in National Standardization - Siti Nur Lutfiyatul Kharisma; Muhammad Fathur Rozaq (Jurnal test, 2026)
This article examines the historical transmission networks of qirāʾāt (Quranic recitation variants) from Arab centers to contemporary Indonesia through a socio-historical and network analysis framework. Utilizing Azyumardi Azra’s ulama network theory and Harald Motzki’s common link methodology, this study investigates why Ḥafṣ ʿan ʿĀṣim became nationally standardized while other readings persist in specialized communities. Through library research on classical manuals (al-Shāṭibiyyah, al-Ṭayyibah), prosopographical analysis of Indonesian qurrāʾ (Aceh, Banten, Java), and document examination of curricula, mushaf standardization, and digital pedagogy, data are analyzed descriptively, critically, and comparatively to map transmission phases, nodes, and flows. Findings reveal that transmission operates through multi-layered mechanisms: face-to-face (talaqqī–musyāfahah), institutional ecosystems (pesantren, LPTQ/JQH), and material regimes (printing, competitions, curricula). Ḥafṣ dominance emerges from the convergence of dense personal isnād chains, twentieth-century print standardization, and curricular alignment, while Warsh and Qālūn persist as advanced specializations. This study introduces “institutional isnād” as a concept linking personal chains with policy and publishing systems, and proposes an evolutionary timeline from early codification to digital re-globalization, offering implications for multi-qirāʾāt curriculum design and teacher certification frameworks.